The inflamed sputum in lower respiratory tract infection: l‐lactate levels are correlated to neutrophil accumulation. Issue 2 (6th January 2019) - Fredman, Gabriella; Kolpen, Mette; Hertz, Frederik Boetius; Petersen, Pelle Trier; Jensen, Andreas Vestergaard; Baunbæk‐Egelund, Gertrud; Ravn, Pernille; Jensen, Peter Østrup; Faurholt‐Jepsen, Daniel
Abstract : Lower respiratory tract infections (LRTI) are common, but little is known about the response of biomarkers of inflammation in the lungs. Therefore, our primary aim was to compare the concentration ofl ‐lactate to the concentration of neutrophils in sputum and systemic markers of infection. Because it is difficult to differentiate viral and bacterial infection on the basis of clinical presentation in LRTI, our secondary aim was to evaluate ifl ‐ andd ‐lactate may serve as markers of local inflammation as representatives of neutrophils and bacteria, respectively. Methods: Patients with acute LRTI were prospectively recruited. Sputum samples were collected and analysed for neutrophil count, l ‐lactate andd ‐lactate. We had data on pathogens from sputum cultures and polymerase chain reaction (PCR) (atypical bacteria, virus) and C‐reactive protein (CRP) from blood. Results: In 44 sputum samples from 32 patients, the median (interquartile range (IQR)) sputum neutrophil granulocyte count was 0.615 × 10 7 cells/mL (0.236–1.575). The sputum neutrophil granulocyte count was associated with sputuml ‐lactate (p = 0.011) and CRP (p = 0.018), but not withd ‐lactate (p = 0.177). There was a strong association between sputumd ‐lactate andl ‐lactate (p < 0.0001). Conclusion: Asl ‐lactate in sputum is closely correlated to sequestration of neutrophils in the lungs, l ‐lactate is a marker for local inflammation in LRTI and a potential biomarker in clinical management of LRTI. On expectorated sputum, d ‐lactate had no clinical relevance.